Treasured Strangers: Race, Biopolitics, and the Human in Octavia E. Butler’s XENOGENESIS Trilogy. - Dowdall, Lisa (Science Fiction Studies, 2017)
The XENOGENESIS trilogy, written during a period of rapid growth in the neoliberal bioeconomy in the United States, is increasingly relevant today, when our ability to manipulate life has outstripped the ethical and theoretical considerations of reproductive/genetic research and technologies. In this essay I seek to bring the trilogy into conversation with a broader dialogue around reproduction in relation to race, drawing on discussions of scientific racism and medical apartheid. Butler’s work draws on a variety of biopolitical discourses and is deeply concerned with the figure of the black woman as breeder, the history of reproduction as eugenics, and the contemporary “tissue economies” (Waldby and Mitchell) that continue to exploit the reproductive labor of non-white and third-world bodies. The XENOGENESIS trilogy illuminates the links between colonialism and biological capital, and uses apocalypse to show how the “human” is constantly being discursively and biologically reconstructed. By contrasting the genetic determinism of the Oankali with humans’ insistence on biological and reproductive independence, Butler enacts a politics of ambivalence that situates reproduction as an ongoing dialectical process within the context of broader ecological systems. Although her work is certainly concerned with genetic engineering, she emphasizes the importance of generation rather than reproduction, articulating a theory of symbiogenesis that sees human evolution as reliant on dynamic relationships with other species and environments.